2002
DOI: 10.1046/j.1463-1318.2002.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery – lessons from a single UK centre series

Abstract: Although longer term follow up is still required, TEM appears to be an effective method of excising benign tumours and T1 carcinomas of the rectum. The role of TEM in the treatment of T2 carcinomas is, as yet, unclear and needs further evaluation although the results of our series and others are encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 20 publications
8
26
0
Order By: Relevance
“…Various published studies have shown a shorter length of hospitalisation in patients undergoing TEM, with an average in patient stay of around 5 days (range 3–8.2) [5, 9, 18,23,24,25, 28,30,31,32,33,34,35,36,37]. This compares favourably with 14.5 days quoted for open procedures [25].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Various published studies have shown a shorter length of hospitalisation in patients undergoing TEM, with an average in patient stay of around 5 days (range 3–8.2) [5, 9, 18,23,24,25, 28,30,31,32,33,34,35,36,37]. This compares favourably with 14.5 days quoted for open procedures [25].…”
Section: Resultsmentioning
confidence: 87%
“…Several published reports have consistently demonstrated these benefits [5, 9, 18,23,24,25,26,27,28,29,30,31,32,33], which hold true for both the older and the younger patients.…”
Section: Resultsmentioning
confidence: 88%
“…1.7 3.5 d.n.o Neary et al [24] 21 0 4.7 d.n.o Katti et al [25] 58 7 10 34 Vorobiev et al [26] 113 -8.3 29.5 Bretagnol et al [27] 148 14.9 7.6 33 Endreseth et al [28] 64 20 13 24 Zacharakis et al [29] 48 4.2 6.3 37 Schäfer et al [30] 33 18 12 36.4 Røkke et al [31] 56 10 0 12 Guerrieri et al [32] 530 -4.3 44 McCloud et al [33] 75 37.3 16 31 Whitehouse et al [34] 146 5.5 4.8 39 Platell et al [35] 62 -2.4 24 Lloyd et al [36] 68 9 5.9 28.7 Ganai et al [37] [31] did not observe adenoma recurrence after 12 mo follow-up in a series of patients in whom the residual adenoma in surgical margin was 10%.…”
Section: Followup (Mo)mentioning
confidence: 99%
“…Nevertheless, these techniques demand experience and, in consequence, must be performed in reference centers where a larger number of patients are available, facing that the surgeon training is mandatory and the small frequency of the indications is a reality [41][42][43][44]. Because of the necessity of having specific instruments and also the particular technical aspects, this method demands good training for the obtention of satisfactory results [45][46][47]. It was described that in 11 tumors located up to 4 cm of the anorectal line, a surgical conversion was necessary because of technical difficulties [48].…”
Section: Discussionmentioning
confidence: 99%